Inhibition of Leishmania (Leishmania) amazonensis growth and infectivity by aureobasidin A - Tanaka, Ameria K. [UNIFESP] (2007)
Objectives: To study the effect of aureobasidin A, an inhibitor of inositol phosphorylceramide (IPC) synthase, on Leishmania growth and infectivity.Methods: Effects of aureobasidin A were determined for: (i) promastigote growth in axenic culture; (ii) promastigote infectivity in macrophage monolayers; (iii) development of footpad lesions in BALB/c mice; (iv) differentiation of amastigotes into promastigotes.Results: Aureobasidin A (20 mu M) inhibited 90% of Leishmania (Leishmania) amazonensis promastigote growth in axenic culture, but the parasites remained viable, i.e. growth curves returned to normal after aureobasidin A was removed from culture medium. the aureobasidin A IC50 was determined by MTT assay as 4.1 mu M for L. (L.) amazonensis promastigotes, 12.6 mu M for Leishmania (Leishmania) major and 13.7 mu M for Leishmania (Viannia) braziliensis. There was a significant delay in infection when L. (L.) amazonensis promastigotes pre-treated with aureobasidin A were inoculated into BALB/c mouse footpads. When aureobasidin A was added to cultured macrophages infected with amastigotes, the number of infected macrophages was reduced by >90%.Conclusions: Aureobasidin A is an interesting pharmacological tool to investigate the effect of lipid metabolism inhibition in Leishmania spp.